Assessment of the physicochemical and bacteriological quality of water source and a well in Bakoya aquifer, northern Morocco - Benaissa, Chaimae; Rossi, Abdelhamid; Bouhmadi, Belkacem; El Hammoudani, Yahya; Dimane, Fouad (E3S web of conferences, 2024)
This study aims to investigate the physical, chemical, and bacteriological quality of water derived from both a well and a spring across three distinct periods (2008, 2012, and 2021) in both summer and winter. These sampling points are situated within the urbanized area of Al Hoceima and serve as crucial sources of drinking water for a substantial portion of the city's population due to their proximity to the city center. The water hardness values observed at these natural points ranged from 5.9 to 82 (°F), categorizing the water from these sources as very hard. Furthermore, the Piper diagram revealed chemical facies characterized by chlorinated sodium and calcium magnesium sulfate. The elevated concentrations of sodium and chloride were attributed to the proximity of the Mediterranean Sea shoreline. Analysis of bacteriological parameters in these waters uncovered notable contamination by fecal germs. Principal Component Analysis (PCA) of the water samples identified two primary groups, elucidated by two factors that collectively account for 79.37% of the variance. The first factor (50.11%) is linked to gypsum dissolution and marine intrusion, while the second factor (29.26%) is associated with external contributions such as anthropogenic pollution.